2021
DOI: 10.32598/irjns.7.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Non-aneurysmal Perimesencephalic Subarachnoid Hemorrhage in A COVID-19 Patient: Case Report and Review on Subarachnoid Hemorrhage Patterns in COVID-19

Abstract: Background and Importance: The novel SARS-CoV-2 virus has had an undeniable effect worldwide in different aspects. Although cerebrovascular diseases, especially subarachnoid hemorrhage (SAH), have already been reported in COVID-19 patients, little is known about various types and patterns of SAH in these patients. Case Presentation: A 63-year-old woman was admitted to the emergency department with a headache. Her headache was severe (Hunt and Hess score, grade 2). She was diagnosed with COVID-19 by a positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Numerous reports of viral infections and nonaneurysmal SAH have been associated with COVID-19 caused by SARS-CoV-2, [1][2][3][4]6,7,9,12,16,17,23,24] while some have been associated with other viruses including human immunodeficiency virus, herpes simplex virus, Epstein-Barr virus, Jamestown Canyon virus, and varicella zoster virus. [10,15,21,[25][26][27] Interestingly, there have been no reports of nonaneurysmal SAH caused by coronaviruses other than SARS-CoV-2, such as severe acute respiratory syndrome coronavirus 1 (SARS-CoV-1 or simply SARS-CoV) and Middle East respiratory syndrome…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports of viral infections and nonaneurysmal SAH have been associated with COVID-19 caused by SARS-CoV-2, [1][2][3][4]6,7,9,12,16,17,23,24] while some have been associated with other viruses including human immunodeficiency virus, herpes simplex virus, Epstein-Barr virus, Jamestown Canyon virus, and varicella zoster virus. [10,15,21,[25][26][27] Interestingly, there have been no reports of nonaneurysmal SAH caused by coronaviruses other than SARS-CoV-2, such as severe acute respiratory syndrome coronavirus 1 (SARS-CoV-1 or simply SARS-CoV) and Middle East respiratory syndrome…”
Section: Discussionmentioning
confidence: 99%
“…A literature review revealed 16 cases of nonaneurysmal SAH associated with COVID-19 infection, including ours [ Table 1 ]. [ 1 - 4 , 6 , 7 , 9 , 12 , 16 , 17 , 23 , 24 ] The average age of onset for nonaneurysmal SAH associated with COVID-19 infection was 57 years, similar to SAH due to cerebral aneurysm rupture. There was no gender difference in COVID-19-associated nonaneurysmal SAH, while SAH due to cerebral aneurysm rupture seems to be more common in women.…”
Section: Discussionmentioning
confidence: 99%